Contemporary challenges of transport systems and traffic engineering : 13th Scientific and Technical Conference "Transport Systems, Theory and Practice 2016" Katowice, Poland, September 19-21, 2016 selected papers /: 13th Scientific and Technical Conference "Transport Systems, Theory and Practice 2016" Katowice, Poland, September 19-21, 2016 selected papers. ([2017]) - Unknown
No abstract available